Heavy helper bucket mover / Nur Fatin Aniesya Azizul Aziz - Azizul Aziz, Nur Fatin Aniesya (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
An untreated, severe slipped disc can lead to permanent nerve damage. In very rare cases, a slipped disc can cut off nerve impulses to the cauda equina nerves in your lower back and legs. If the herniated disc is not pressing on a nerve, the patient may experience a low backache or no pain at all. If it is pressing on a nerve, there may be pain, numbness or weakness in the area of the body to which the nerve travels. This is where the “Heavy Helper Bucket Mover” comes in, a customized detachable roller platform for people with slip disc for transporting heavy items during everyday activities. Sometimes, the user needs assistance carrying heavy items or cannot bend over to pick up items because of painful flare-ups that interrupt daily activities. Using the textured platform to help support the weight of heavy items can help the user avoid any unnecessary strain on their spine. This way, the user can have more independence without needing to rely on another person to carry their items. With it’s durable, portable, and lightweight design, the “Heavy Helper Bucket Mover” is sure to be of assistance when the user is in need.